1994
DOI: 10.1007/bf00599514
|View full text |Cite
|
Sign up to set email alerts
|

Changes in muscle oxygenation during weight-lifting exercise

Abstract: The quantitative analysis of haemoglobin oxygenation of contracting human muscle during weight-lifting exercise was studied noninvasively and directly using near-infrared spectroscopy. This method was developed as a three-wavelength method which confirmed the volume changes in oxygenated haemoglobin (oxy-Hb), deoxygenated haemoglobin (deoxy-Hb) and blood volume (total-Hb; Oxy-Hb+deoxy-Hb). Nine healthy adult men with various levels of training experience took part in the study. Ten repetition maximum (10 RM) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…Collins et al (1991) have suggested increased intra-thoracic and abdominal pressures during RL as factors that limit venous return. It has also been hypothesized that the isometric contractions involved in holding the load and maintaining control of the trunk during RL could result in reduced blood¯ow to the exercising muscle tissue, thus reducing the maximum utilization of oxygen (Reybrouk et al 1975;Tamaki et al 1994). These data clearly illustrate that volitional fatigue for RL is attained at a lower O 2 than for TR for both men and women, and this fact should be considered when determining acceptable work intensities for RL exercise (McGill et al 1995;Petrofsky and Lind 1978a;Sharp et al 1988).…”
Section: Discussionmentioning
confidence: 87%
“…Collins et al (1991) have suggested increased intra-thoracic and abdominal pressures during RL as factors that limit venous return. It has also been hypothesized that the isometric contractions involved in holding the load and maintaining control of the trunk during RL could result in reduced blood¯ow to the exercising muscle tissue, thus reducing the maximum utilization of oxygen (Reybrouk et al 1975;Tamaki et al 1994). These data clearly illustrate that volitional fatigue for RL is attained at a lower O 2 than for TR for both men and women, and this fact should be considered when determining acceptable work intensities for RL exercise (McGill et al 1995;Petrofsky and Lind 1978a;Sharp et al 1988).…”
Section: Discussionmentioning
confidence: 87%
“…Previously, ROS have been shown to promote growth in both smooth and cardiac muscle [82], and it is theorized that similar hypertrophic effects may occur in skeletal muscle [13,41,83]. However, while the activity of ROS within muscle is known to increase in ischemic conditions, particularly upon reperfusion [84], previous research by Takarada et al [8] reported no change in lipid peroxide levels following lowintensity resistance exercise either with or without BFR.…”
Section: Intramuscular Signallingmentioning
confidence: 99%
“…Several studies have examined muscle oxygenation trends during static contractions of dierent muscle groups including the knee¯exors and extensors (Sahlin 1992), elbow¯exors (Kahn et al 1998) and forearm muscles (DeBlasi et al 1993). The changes in muscle oxygenation during dynamic resistance exercise (biceps curls) have also been reported (Tamaki et al 1994). Currently, there is minimal research pertaining to the trends in muscle oxygenation during high intensity anaerobic exercise.…”
Section: Introductionmentioning
confidence: 97%